Data huggers. (Economist, 2012)
The article focuses on the DataKind, a charitable organization where computer experts work to make other charities more productive through data analytics. Topics include the types of charities the volunteers work with, how the data analytics help to show donors how their money is spent, and why the volunteers believe that volunteering helps them as well.